Computational Study of Coordinated Ni(II) Complex with High Nitrogen Content Ligands. (4th April 2011) - Tang, Bo; Ye, Jia-Hai; Ju, Xue-Hai
Abstract : Density functional computations were performed on two tetracoordinated Ni(II) complexes as high nitrogen content energetic materials (1 : dinickel bishydrazine ter[(1 H -Tetrazol-3-yl)methan-3yl]-1 H -tetrazole and2 : dinickel tetraazide ter[(1 H -Tetrazol-3-yl)methan-3yl]-1 H -tetrazolate). The geometrical structures, relative stabilities and sensitivities, and thermodynamic properties of the complexes were investigated. The energy gaps of frontier molecular orbital (HOMO and LUMO) and vibrational spectroscopies were also examined. There are minor Jahn-Teller distortions in both complexes1 and2, with two long Ni–N bond lengths and two short ones. The enthalpies of combustion for both complexes are over 3600 kJ/mol. The N–N bond lengths in the moieties of hydrazine and azide ligands increase in the coordination process compared to those of the isolated molecules.